2016
DOI: 10.3390/met6060126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Warm Laser Peening on Thermal Stability and High Temperature Mechanical Properties of A356 Alloy

Abstract: Abstract:To study the effects of warm laser peening (WLP) on the thermal stability and mechanical properties of A356 alloy, the samples were treated by WLP using a Nd:YAG solid-state laser and temperature control device. The residual stress, micro-hardness and microstructures of samples treated by WLP were observed. The result shows that the temperature significantly affects the strengthening effect of laser peening (LP). The residual stress induced by WLP decreases with the increasing temperature. The micro-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Many dislocations tangled to strengthening precipitates are also shown, which are assumed by Huang et al [4] to be beneficial for improving residual stress stability. This last aspect was confirmed for a similar WLP procedure by Chen et al [5], considering an A356 (Al7Si0.3Mg) cast aluminum alloy. After a 220 • C-100 min thermal treatment, WLP samples exhibited more stable residual stress fields than room temperature peening.…”
Section: Warm Laser Peening Applied To Aluminum Alloyssupporting
confidence: 66%
See 1 more Smart Citation
“…Many dislocations tangled to strengthening precipitates are also shown, which are assumed by Huang et al [4] to be beneficial for improving residual stress stability. This last aspect was confirmed for a similar WLP procedure by Chen et al [5], considering an A356 (Al7Si0.3Mg) cast aluminum alloy. After a 220 • C-100 min thermal treatment, WLP samples exhibited more stable residual stress fields than room temperature peening.…”
Section: Warm Laser Peening Applied To Aluminum Alloyssupporting
confidence: 66%
“…The following fields are covered in the seven selected papers: materials' behavior and phase transformations under high strain rate (Amadou et al [1]), new loading conditions with ultra-short pulses (Petronic et al [2]) surface modifications induced by laser peening including recrystallization effects (Zhou et al [3]) and warm laser peening (Huang et al [4], Chen et al [5]), and novel applications of LSP such as water droplet erosion resistance (Gujba et al [6]) or impact spot welding (Liu et al [7]). The wide variety of topics related to LSP highlights the extraordinary dynamism and enthusiasm of the growing international LSP community.…”
Section: Introduction and Scopementioning
confidence: 99%
“…According to the review, a dislocation pinning effect based on the dynamic strain aging (DSA) and dynamic precipitation (DP) is the main reason for improvement of residual stress and microstructure stability of WLSP [14,15]. Chen et al [16] in Jiangsu University studied the effects of warm laser peening (WLP) on thermal stability of the A356 alloy and found that WLP can effectively improve the thermal stability of residual stress compared with LP. From 2011 to 2015, Ye et al [17][18][19] studied the effect of CLSP on the mechanical properties of copper and 304 stainless steel; it was found that due to the generation of nanotwinned microstructure during CLSP, the strength and ductility of the materials could be improved simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal-mechanical coupling effect was used to optimize the microstructures on material surface treated by WLSP, so as to obtain more stable residual stress field and mechanical properties than RT-LSP, such as material strength, modulus of elasticity, fatigue strength, etc. [12,13]. Taking AA6061 aluminum alloy as the research object, Liao et al [14] investigated the stability of CRS induced by RT-LSP and WLSP under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%